Análise da percepção ambiental na comunidade apiques (Itapipoca/CE): Um enfoque de gênero. - Morais, Tiala Cristine de Albuquerque de (2012)
The discussions on gender and the environment suggest a strong relationship between women and environmental issues. Sometimes this relationship is seen as the female innate characteristic and others as a social construction. In this perspective, the objective was to analyze the environmental perception of women and men living in the community Apiques, located in Maceió Settlement Itapipoca Municipality (EC). It was adopted as instruments to collect data through observation, questionnaires and interviews. The main results showed that it is not possible to conclude that women perceive the environment better than men. There was a strong degree of similarity to the perception of women and men, however, the reasons why men and women consider important the environment is different and interesting elements to show the reflection of gender. In their speeches the women worry about the future of the children and the community, concerned about the scarcity of natural resources in the future and the consequences that this may cause shortages in the community. It is believed that the differences between the environmental perception of women and men are a reflection of the gender system experienced not only influences the environmental perception of both sexes, and keeps women in conditions of subordination. This reality points to the need of public and environmental policies that incorporate the gender dimension, seeking to promote the breakdown of the various forms of oppression.